2020
DOI: 10.3389/fnut.2020.00114
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Healthy Eating Promotion and Behavioral Change Perceived as Effective by Nutrition Professionals: A Mixed-Methods Study

Abstract: Nutrition professionals may recognize ways to improve diet among their clients/patients. This study aimed to survey strategies and foods that nutrition professionals in Puerto Rico perceive as most effective for healthy eating promotion and behavioral change. The study was a cross-sectional online mixed-methods survey conducted among registered members of the College of Nutritionists and Dietitians of Puerto Rico. Using close-ended questions, nutrition professionals identified foods that they considered as eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 48 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…Participant intake of sugar-sweetened beverages did not change at all, suggesting that additional emphasis on non-sugar-sweetened beverage alternatives be added to the curriculum. A recent study examining strategies for promotion of healthy eating found that sugary beverages were among the most difficult “foods” to control, and that gradual (small) dietary changes were among the strategies found to be most effective [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participant intake of sugar-sweetened beverages did not change at all, suggesting that additional emphasis on non-sugar-sweetened beverage alternatives be added to the curriculum. A recent study examining strategies for promotion of healthy eating found that sugary beverages were among the most difficult “foods” to control, and that gradual (small) dietary changes were among the strategies found to be most effective [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nutritionists and dietitians surveyed in PR considered legumes as a food easy to include in the diet of Puerto Ricans. In contrast, fats and fried foods were deemed challenging to control or decrease, suggesting that a shift toward healthy fats may be feasible rather than a reduced-fat diet [ 88 ]. Although olive oil is widely available in PR, in 2019 an ounce of olive oil cost $0.24 vs. $0.08 USD for canola or soybean oil.…”
Section: Study Protocolsmentioning
confidence: 99%
“…The adaptation for the materials in the intervention group was guided by published literature and formative research conducted by the study team [ 17 , 75 , 88 ]. The adaptation included deep-structure strategies that have been considered useful and culturally appropriate for healthy eating in this population.…”
Section: Study Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Health improvement and disease prevention stand out as motives to follow a personalised nutrition intervention (29), especially among people with existing NCD (such as diabetes) (30). The degree of personalisation (31), attention to coaching and monitoring (32), and the involvement of professional nutritionists (29) are drivers of effectiveness. Furthermore, there is a level of community reinforcement due to the general belief that people have responsibility to look after their health (33).…”
Section: Literature Review Of Previous Studiesmentioning
confidence: 99%